Kuwentong bayan noong panahon ng Hapon : everyday life in a time of war - Kintanar, Thelma B.; Aquino, Clemen C.; Arinto, Patricia B.; Camagay, Ma. Luisa T. (University of the Philippines Press, 2006)
History of the social conditions during Japanese occupation in the Philippines.